ANALISIS PENGARUH MOTIVASI, STRES KERJA, DAN KOMPENSASI TERHADAP KINERJA PILOT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. WINGS ABADI AIRLINES - Sufyati H.S; Muhamad Ujang Hudromi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to analyze the effect of motivation, job stress, and compensation onjob satisfaction and pilot performance at PT. Wings Abadi Airlines. The analyticalmethod used is descriptive and inferential analysis with the method of StructuralEquational Model (SEM). The results of the research are motivation andcompensation have a positive and significant effect on job satisfaction andperformance, work stress has a negative and insignificant effect on job satisfaction,job stress has a positive and insignificant effect on job satisfaction, job satisfactionhas a positive and significant effect on performance, motivation and compensation.positive and significant effect on employee performance through job satisfaction